Report submitted to the W.K. Kellogg Foundation on the Third Year of Operation if the Grant to Demonstrate the significant contribution that rural young people can make to rural development in Latin America - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
280 páginas